Peningkatan Religiusitas pada Anak di Masa Pandemi Covid-19 - Hidayati, Nur (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Children are an asset of a nation, children as a part of the younger generation play a very strategic role as the successor of a nation. Therefore, it is very important to instill Islamic religious values from an early age in children so that they can create good and quality personalities in the future. The purpose of this research and service is to find out the efforts that can be made to improve the quality and religiosity of children. The service method used by the author is the PAR (Participatory Action Research) method, which is a community service method in the form of research and carried out with participation with activities in the community within a social and community sphere in order to make change actions for the better. From the results of this study, it was found that by instilling religious values in children through habits such as praying in congregation in mosques, providing knowledge about the Islamic religion, and also providing interesting activities, it can increase children's enthusiasm for learning and it is easier to absorb values well delivered.